Kepuasan Penggunaan Telemedicine terhadap Keputusan Penggunaan Telemedicine di RSU X Kabupaten Malang - Ayu, Jennyla Puspitaning (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2024)
Patients feel dissatisfied when using telemedicine because they feel that the telemedicine service has too many menus, is not clear and is not easy to use. The research design used in this research is a cross-sectional method and is a quantitative study. This research was conducted on patients at the Outpatient Installation of Hospital The sample obtained for this research was 209 people. The data collection technique uses a questionnaire method with a Linkert measurement scale. Data analysis in this study used the Spearman Rank correlation test. The results of the Spearman Rank analysis statistical test in this study to determine the relationship between satisfaction with using telemedicine services and the decision to use telemedicine services at RSU X Malang Regency showed a coefficient value of 0.827. Based on the results of hypothesis testing in this study, it can be concluded that there is a relationship between patient satisfaction (X) and reuse of telemedicine services (Y). Improving the quality of telemedicine, ease of communication and comfort need to be considered, in order to provide patient satisfaction in using telemedicine services and will have an impact on the reuse of these services.